PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF UNTUK PESERTA DIDIK KELAS IV SEKOLAH DASAR - Aulia Sholihah; Nana Hendracipta; Odin Rosidin (LPPM Universitas Cipta Mandiri, 2025)
This research is motivated by the lack of interesting and interactive learning media variations that can improve students' understanding and motivation towards learning materials. This study aims to develop interactive powerpoint learning media used in the learning process of grade IV elementary school students. The method used is research and development (R&D) with a 4D model consisting of 4 stages, namely: define, design, develop, and dissimimate. This study uses an instrument in the form of a questionnaire in collecting data, the lifting sheets used are: media expert questionnaire, language expert questionnaire, material expert questionnaire and student response questionnaire. The results of the media expert validation showed a percentage of 87.36% with the category